1991
DOI: 10.1152/ajpgi.1991.260.3.g385
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide mediating NANC inhibition in opossum lower esophageal sphincter

Abstract: Strips from opossum lower esophageal sphincter were prepared and mounted in organ baths for recording of isometric tension. Nonadrenergic, non-cholinergic (NANC) inhibitory responses were evoked by transmural field stimulation. The relaxant responses to field stimulation were inhibited in a concentration-dependent manner by N omega-nitro-L-arginine (L-NNA), a substance known to inhibit the formation of nitric oxide (NO). At a concentration at 10(-4) M of L-NNA, most preparations contracted during field stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 0 publications
4
80
1
2
Order By: Relevance
“…Moreover, relaxant responses to forskolin and SNP, stimulators of adenylate and guanylate cyclase, respectively (Seamon et al, 1981;Rapoport & Murad, 1983), were unaffected by L-NNA preincubation, indicating that the inhibitory effect of L-NNA was not due to a direct effect on these enzymes. In this particular tissue, however, we found that the L-arginine-NO pathway apparently plays a less prominent role for relaxation, as L-NNA in the applied concentrations had a more pronounced effect on NANC-mediated relaxations in some other tissues studied (Li & Rand, 1989;Hobbs & Gibson, 1990: T0ttrup et al, 1991aT0ttrup et al, 1992). Further support is added to these considerations, as L-NNA did not shift the frequencyresponse curve, implying a non-competitive nature of L-NNA on inhibitory responses, and thus, suggesting the action of at least one other inhibitory NANC mediator.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, relaxant responses to forskolin and SNP, stimulators of adenylate and guanylate cyclase, respectively (Seamon et al, 1981;Rapoport & Murad, 1983), were unaffected by L-NNA preincubation, indicating that the inhibitory effect of L-NNA was not due to a direct effect on these enzymes. In this particular tissue, however, we found that the L-arginine-NO pathway apparently plays a less prominent role for relaxation, as L-NNA in the applied concentrations had a more pronounced effect on NANC-mediated relaxations in some other tissues studied (Li & Rand, 1989;Hobbs & Gibson, 1990: T0ttrup et al, 1991aT0ttrup et al, 1992). Further support is added to these considerations, as L-NNA did not shift the frequencyresponse curve, implying a non-competitive nature of L-NNA on inhibitory responses, and thus, suggesting the action of at least one other inhibitory NANC mediator.…”
Section: Discussionmentioning
confidence: 67%
“…Following the description that the smooth muscle composition of the NA opossum lower esophageal sphincter, in contrast to that of more common laboratory animals (rats, cats and dogs), resembles more closely the human lower esophageal sphincter (13) most of the current concepts regarding the neural control of gastrointestinal sphincters were derived from in vivo and in vitro studies performed on this animal model (3)(4)(5)(6)(7)(8)14,15). Since this opossum species is not readily available to us, in the present study we characterized in vitro the nerve-induced responses of the circular smooth muscle from gastrointestinal sphincters of the closely related opossum species Didelphis albiventris, readily available in SA.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence accumulated during the last three decades indicates that nerves mediating such responses employ neither noradrenaline nor acetylcholine as a neurotransmitter and consequently are referred to as nonadrenergic noncholinergic (NANC) nerves (2). Experiments designed to elucidate the mediator and mechanisms involved in NANC nerve-induced relaxations of sphincteric muscle in the gastrointestinal tract have been performed mainly in North American (NA) opossums (Didelphis virginiana) (3)(4)(5)(6)(7)(8) or in dogs (9)(10)(11)(12). The properties of opossum gastrointestinal sphincters are closer to the human ones as compared to dogs and cats (13) but NA opossums are not readily available in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Enteric motoneurons (EMNs) are the final step in the inhibitory vagal pathway to the LES, mediating swallow-induced and transient LES relaxation (3). Nitric oxide (NO) released from these inhibitory EMNs is the major contributor to LES relaxation in humans (12) and opossums (20,33). However, vasoactive intestinal peptide (VIP) and ATP are putative inhibitory neurotransmitters in animal studies (14, 21-24, 34, 37, 39), and the relative contribution of each of these neurotransmitters remains unclear in humans.…”
mentioning
confidence: 99%